ANALISIS MANAJEMEN LABA DAN RELEVANSI NILAI LABA SEBELUM DAN SELAMA PANDEMI COVID-19 - Nur Annisa Sekaranti; Agung Juliarto (Diponegoro Journal of Accounting, 2022)
This study aims to analyze earnings management practices and the value relevance of earnings before and during the Covid-19 pandemic. Earnings management was measured using discretionary accruals using the Modified Jones model (Dechow et al., 1995) and value relevance of earnings was measured by Ohlson model.This study uses 138 manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2020. The purposive sampling method was used for sample selection in this study. The data used is secondary data obtained from the annual reports available on the IDX website and the Yahoo Finance websitethe data were analyzed using the Wilcoxon Signed Ranks Test to find out the differences ini earnings management practices and compare the cofficients of determinations for the value relevance of earnings before and during the Covid-19 pandemic.Based on the results of statistical tests, this study showed that there were no significant differences in earnings management practices before and during the Covid-19 pandemic, although there was an increase of earnings management practices in 79 manufacturing companies. In addition, this study found that the value relevance of earnings decreased from the year before (2019) to the year during (2020) Covid-19 pandemic. Therefore Covid-19 pandemic does not make any difference in the earnings management practices, but reduces the usefulness of the value of accounting information from value relevance of earnings